A trimeric DNA polymerase complex increases the native replication processivity - Mikheikin, Andrey L. (Oxford University Press, 2009)
DNA polymerases are essential enzymes in all domains of life for both DNA replication and repair. The primary DNA replication polymerase from Sulfolobus solfataricus (SsoDpo1) has been shown previously to provide the necessary polymerization speed and exonuclease activity to replicate the genome accurately. We find that this polymerase is able to physically associate with itself to form a trimer and that this complex is stabilized in the presence of DNA. Analytical gel filtration and electrophoretic mobility shift assays establish that initially a single DNA polymerase binds to DNA followed by the cooperative binding of two additional molecules of the polymerase at higher concentrations of the enzyme. Protein chemical crosslinking experiments show that these are specific polymerase–polymerase interactions and not just separate binding events along DNA. Isothermal titration calorimetry and fluorescence anisotropy experiments corroborate these findings and show a stoichiometry where three polymerases are bound to a single DNA substrate. The trimeric polymerase complex significantly increases both the DNA synthesis rate and the processivity of SsoDpo1. Taken together, these results suggest the presence of a trimeric DNA polymerase complex that is able to synthesize long DNA strands more efficiently than the monomeric form.